Peningkatan Kemampuan Berpikir Kreatif Dengan Menggunakan Model Treffinger Pada Siswa Kelas V SDN 024 Limau Manis - Larahati, Putri Rizka; Aprinawati, Iis; Ananda, Rizki; Pebriana, Putri Hana (Universitas Negeri Makassar, 2023)
. This research is motivated by the low creative thinking ability of fifth grade students at SDN 024 Limau Manis. The subject of this researchis the fifth grade studenst of SDN 024 Limau Manis, totaling 9 students with 6 male students and 3 famale students. The results of this study can be concluded that the creative thinking ability of fifth grade students at SDN 024 Limau Manis has increased in each cycle. Whre the percentage results in cycle I meeting I reached (44%) and in cycle I meeting II increased to (55%) while in cycle II meeting I it reached (66%) and in cycle II meeting II it increased to (88%). Thus it can be concluded that using the Treffinger model can improve students creative thinking skills in class fifth grade students at SDN 024 Limau Manis.